PLANFORM OF MANTLE CONVECTION BENEATH THE PACIFIC-OCEAN - Mckenzie, D; Watts, A; Parsons, B; Roufosse, M (1980)
The correlation between variations of the bathymetry and of the geoid in the Pacific Ocean suggests that both are the surface expression of mantle convection. The planform of the convection which is required to generate the observed anomalies does not consist of rolls but is three dimensional, with rising and sinking jets elongated in the direction of motion of the Pacific plate relative to the frame of reference defined by the hot spots. The spacing between the maxima and minima of the geoid is between 1,500 and 2,000 km and hence favours a model of mantle convection with multiple scales of circulation. © 1980 Nature Publishing Group.